RECURRENT MALIGNANT TUMORS OF THE EYELID - I. E. Panova; A. E. Arakelyan; I. A. Kuchenkova (Опухоли головы и шеи)
This article is based on the work results of a specialized oncoophtalmology center. The data on frequency, structure and disease course characteristics of recurrent malignant tumors of the eyelid among 1657 patients during 14-year follow up is presented; the relationship between relapse frequency and treatment is established. Basal cell carcinoma was found to prevail in the relapse cases. We observed a decrease in frequency of recurrence during the study period, which can be explained by implementation of surgical and combined treatment of the disease.